(3GdfXQ Edi GdMGVQ HYjf GdeSJbHds - (3SYO Ydj(B, (3GdeMeOjs ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjY(B,s, 2022)
(3jTed cJGH GdEOGQI GdGSJQGJjLjI QMdI TGedI JHOC HeONd CSGSj ddeaghe Ke JJYeb aj JMdjd GdHjFI GdeMjWI HGdefXeI, ShGA cGfJ OGNdjI Ch NGQLjI, dJMOjO fbGW GdbhI hGdVYa hGdaQU hGdJMOjGJ(B. (3jbOe GdcJGH HYO Pdc COhGJ hNWhGJ dUjGZI GSJQGJjLjGJ eJfhYI hJbjjegG dGNJjGQ GdCaVd, eY GdJQcjR Ydi CgejI GdJfajP GdaYGd ddNWW GdGSJQGJjLjI(B. (3hNJGekG, jJfGhd GdcJGH CgejI GdQbGHI GdeSJeQI ddJCcO ef JMbjb GdCgOGa GdGSJQGJjLjI, hjbOe CeKdI YedjI ef NdGd JMdjd MGdGJ OQGSjI eJfhYI(B. (3gPG GdedNU jZWj GdLhGfH GdQFjSjI ddcJGH, HOkAG ef GdCSGS GdfXQj hUhdkG Edi GdJWHjb GdYedj, eeG jLYdg eQLYkG TGedkG ddOGQSjf hGdeeGQSjf aj eLGd GdEOGQI GdGSJQGJjLjI(B.s
(3GdeQGLY U(B.378s
Keywords: (3GdEOGQI GdESJQGJjLjIs; (3GdJNWjW GdESJQGJjLjs